The Use of Picture Story Media in Improving Students’ Learning Activities and Paragraph Writing Ability - Paryanto, Paryanto; Sutrisno AB, Joko; Maryova, Frieska (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2021)
This study aims to increase learning activities by applying illustrated story media in learning to write Indonesian paragraphs, and to increase learning activities for fifth grade students at SDN Lembasung, Way Kanan Regency, for the 2020/2021 academic year. This study employs Classroom Action Research (CAR) method. To determine the students' ability to write paragraphs, this study uses some data collection techniques, such as observation, documentation, and test. The technique used in this research is a written test technique, which is to obtain data from the test results of each cycle. This written technique is used to determine the ability of students to write paragraphs. All data collected is processed through the following stages: data reduction, data tabulation, and data inference. Based on the analysis of observational data, there is the ability to write paragraphs through illustrated story media in class V SDN Lembasung, Way Kanan Regency in the 2020/2021 academic year in the first cycle, namely the average score obtained. In the pre-action stage, an average score of 138.4, was obtained. the first cycle it increases to 327.2, and in the second cycle it increases to 208.8 with a good category. Therefore, student activity has reached an indicator of the success of student activities increasing, at least well. It can be concluded that there is an increasing ability in writing paragraph through picture story media for the fifth grade students of SDN Lembasung, Way Kanan Regency for the 2020/2021 Academic Year.